2022
DOI: 10.3390/molecules27154685
|View full text |Cite
|
Sign up to set email alerts
|

UHPLC-Q-Orbitrap-MS-Based Metabolomics Reveals Chemical Variations of Two Types of Rhizomes of Polygonatum sibiricum

Abstract: The rhizomes of Polygonatum sibiricum are commonly consumed as food and also used as medicine. However, the metabolic profile of P. sibiricum has not been fully revealed yet. Recently, we developed a novel evergreen species of P. sibiricum. The objectives of this study were to compare the metabolic profiles of two types of P. sibiricum, i.e., the newly developed evergreen type (Gtype) and a wide-type (Wtype), by using UHPLC-Q-Orbitrap-MS-based untargeted metabolomics approach. A total of 263 and 258 compounds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Untargeted metabolomic methodologies, involving high-resolution mass spectrometry and chemometric tools, have been effectively employed to analyze the chemical composition of diverse botanical specimens, such as tea leaves ( 26 ) and rhizomes of Polygonatum sibiricum ( 27 ). In this study, an untargeted metabolomic approach utilizing UHPLC-Q-Orbitrap-MS was adopted to comprehensively profile the chemical constituents of ten samples of G. lucidum fruiting bodies.…”
Section: Resultsmentioning
confidence: 99%
“…Untargeted metabolomic methodologies, involving high-resolution mass spectrometry and chemometric tools, have been effectively employed to analyze the chemical composition of diverse botanical specimens, such as tea leaves ( 26 ) and rhizomes of Polygonatum sibiricum ( 27 ). In this study, an untargeted metabolomic approach utilizing UHPLC-Q-Orbitrap-MS was adopted to comprehensively profile the chemical constituents of ten samples of G. lucidum fruiting bodies.…”
Section: Resultsmentioning
confidence: 99%
“…Untargeted metabolomics aims to identify the vast majority of metabolites in the specimen, and has been widely used in plant metabolite profiling to explore the mechanisms causing particular phenotypes. By using untargeted metabolomics, a recent report identified that a number of differentially accumulated metabolites account for the different beneficial health potentials and flavor of two types of P. sibiricum rhizomes ( Luo et al., 2022 ). Besides, combining this approach with high-throughput transcriptome profiling could not only provide detailed description of the gene-to-metabolite network, but also enable the identification of novel genes involved in the regulation of metabolic features.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported diverse pharmacological effects of P. sibiricum , such as anti-aging, anti-diabetic, anti- inflammatory, and anti-tumor effects ( Zhao et al., 2018 ). These beneficial effects could be attributed to the diverse biologically-active compounds accumulated in the rhizome, such as polysaccharides, alkaloids, saponins, and phenolics ( Luo et al., 2022 ). For example, polysaccharides derived from P. sibiricum were shown to significantly alleviate several memory and cognitive impairments as well as aging characteristics in rats fed with the aging reagent D-galactose ( Zheng, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Metabolomics is widely applied for better understanding phenotypic variation [ 27 , 28 ], investigating nutritive values [ 29 ], and stress resistance [ 30 , 31 ]. Luo et al [ 32 ] reported 19 significantly different metabolites causing flavor attributes of the two types of P. sibiricum rhizomes. Masson et al [ 33 ] successfully utilized metabolomics to discriminate 22 Iris rhizomes, and tentatively identified 32 metabolite discriminating markers to distinguish origins of these plants.…”
Section: Introductionmentioning
confidence: 99%